(untitled) (Research, Society and Development, 2021)
The Brazilian State faced throughout the 19th century the challenge of ordering the territory in the interior of the provinces. The political-administrative constitution was presented in a much more complex way as we know it today. If the municipalities are currently subdivided only into districts, previously political, judicial and ecclesiastical powers participated in the territorial ordering and different categories overlapped, generating a complex territorial ordering. The city of Visconde do Rio Branco, located in the southeast of Minas Gerais has its formation process inserted within this context. When it was still populated, it was called Aldeia do Xopotó dos Coroados, and the municipality was created only in 1839 after being dismembered from Pomba under the name of Vila de São João Batista do Presídio. The municipality of Presídio has an important role in consolidating the territoriality of the central portion of the area of the Minas Gerais forest, from its territory 49 municipalities originated. In this sense, the objective of this research is to discuss the evolution of the territorial ordering of the municipality of Visconde do Rio Branco, explaining the different categories that were part of the territorial ordering of the municipality throughout the 19th and 20th century. The methodology adopted was based on bibliographic research and geoprocessing applied to historical cartography. It is hoped that the research can contribute with information and cartographic materials that enrich the historical geography of the municipalities of Visconde do Rio Branco and also of the municipalities that dismembered from their original territory.